Coconut Shell Carbonization Process Using Smokeless Kiln - Rudi Kurniawan Arief; Armila Armila; Arie Liswardi; Hanafi Yahya; Mahammad Salman Warimani; Perdana Putera (Journal of Applied Agricultural Science and Technology, 2023)
Proper processing of coconut shell charcoal can be highly economically and environmentally valuable. The two most common uses of coconut shell charcoal are activated carbon and briquettes, obtained through carbonization. However, traditional carbonization methods involving kilns can produce excessive smoke, polluting the environment and disrupting human activities. A carbonization kiln that produces less smoke is required to address this issue. In this study, a kiln made from a steel drum with a sealer belt was fabricated to trap burning smoke inside the kiln. The results showed that adding this belt effectively reduced the smoke produced, making it more eco-friendly. Regarding charcoal production efficiency, different weigh coconut shells were burnt to produce charcoal. The result showed that burning 25 kg of coconut shell was optimal, producing a 48% charcoal content.